Promotional Comic Video on Human Circulatory System Material for Elementary Schools - I Ketut Rai Suastika; Ni Wayan Rati; Basilius Redan Werang (Mimbar Ilmu, 2024)
Students still need to be fully interested in the learning process. One of the contributing factors is the need for more use of media as a means of the learning process. This research aims to analyze the design and produce valid and practical media. This research is included in the type of development using the ADDIE model. The research subjects were one material expert, one learning media expert, one practitioner/teacher, three students for individual trials, and 9 for small group trials. The data collection method uses a questionnaire. Meanwhile, data analysis techniques use qualitative and quantitative descriptive analysis. The research results show the validity of the media, with the material expert's assessment getting an average score of 4.8, indicating very valid quality, and the learning media expert's assessment getting an average score of 4.82, indicating very valid quality. The practicality analysis carried out by practitioners/teachers obtained an average score of 4.72, which is included in the very valid category. The analysis of individual trials obtained an average score of 4.74, namely the very valid category, and the assessment results of small group trials obtained an average score of 4.72, the very valid category. This means that the developed media is proven valid and practical for learning. This research implies that the novelty of science material in promotional comic video media can hone teachers' abilities in utilizing technological advances to advance education and increase students' interest in learning.